A Low‐Temperature, Solution Processable Tin Oxide Electron‐Transporting Layer Prepared by the Dual‐Fuel Combustion Method for Efficient Perovskite Solar Cells. Issue 13 (9th April 2016) - Liu, Xiao; Tsai, Kai‐Wei; Zhu, Zonglong; Sun, Ye; Chueh, Chu‐Chen; Jen, Alex K.‐Y.
Abstract : Although tin oxide (SnO2 ) has been employed recently as an efficient electron‐transporter to realize highly efficient organometal halide perovskite solar cells (PVSCs), it is still quite challenging to apply it through facile solution‐based synthesis at low enough temperature (<150 °C) to be compatible with the roll‐to‐roll printing on polymer substrates. In this work, a dual‐fuel combustion method has been successfully adapted to modulate the exothermic characteristics and processing temperature (140 °C) of SnO2 to achieve homogeneous and crystalline thin film as efficient electron‐transporting layer for PVSCs. The fabricated SnO2 film not only has high transparency (from 350 nm to near‐infrared region) but also possesses good electron extraction ability, as evidenced by the efficient PL quenching in bilayered SnO2 /CH3 NH3 PbI3 film. By passivating SnO2 surface with a C60 ‐containing self‐assembled monolayer (C60 ‐SAM), a high power conversion efficiency (PCEmax ) of >15% with negligible hysteresis can be achieved in PVSC. This demonstrates the great potential of applying this dual‐fuel combustion process to improve processability and charge‐transporting properties of metal oxides for organic electronics applications. Abstract : A low‐temperature (<150 °C), solution processible SnO2 electron‐transporting layer is prepared via a dual‐fuel combustion method. The fabricated SnO2 shows a decent charge‐collecting capability from perovskite absorber to realize a maximium power conversion efficiency (PCEmax ) of ≈13% of the derived device. By further passivating the SnO2 surface with C60 ‐containing self‐assembled monolayer, an improved PCEmax of >15% with negligible hysteresis is demonstrated.